Safety, reactogenicity, and immunogenicity of a 12-valent pneumococcal non-typeable Haemophilus influenzae protein D-conjugate vaccine in healthy toddlers: results from a phase I, randomized trial - Michael Horn; Ulrich Behre; Magali Traskine; Kurt Dobbelaere; Dorota Borys (Taylor & Francis Group, 2021)
As a stepping stone toward evaluation in infants, the safety and immunogenicity of an investigational 12-valent pneumococcal non-typeable Haemophilus influenzae protein D-conjugate vaccine (12vPHiD-CV) was assessed in toddlers. 12vPHiD-CV contains CRM197-conjugated capsular polysaccharides of serotypes 6A and 19A in addition to capsular polysaccharides of the 10 serotypes in PHiD-CV. In this phase I, double-blind, multicenter study (NCT01485406) conducted in Germany, 61 healthy toddlers aged 12-23 months previously primed with three PHiD-CV doses were randomized (1:1) to receive one dose of 12vPHiD-CV or PHiD-CV. Safety and reactogenicity of 12vPHiD-CV were assessed in terms of occurrence of grade 3 vaccination-related solicited and unsolicited adverse events (AEs) and vaccination-related serious AEs. Immune responses were evaluated 1 month post-vaccination. Grade 3 solicited local AEs (all considered vaccination-related) were reported for two (6.5%, redness) and three (9.7%, swelling) toddlers in the 12vPHiD-CV group and one (3.4%, swelling) in the PHiD-CV group. Grade 3 vaccination-related solicited general AEs were only reported in the PHiD-CV group. No grade 3 unsolicited or serious AEs were reported. For PHiD-CV serotypes, 100% of toddlers in both groups had antibody concentrations ≥0.2 µg/mL 1 month post-vaccination, and antibody geometric mean concentrations increased from pre-boosting. For serotypes 6A and 19A, antibody responses tended to be higher in the 12vPHiD-CV than the PHiD-CV group. A single dose of 12vPHiD-CV administered in toddlers was well tolerated and no safety concerns were identified. Immune responses were comparable to those induced by PHiD-CV when administered in toddlers previously primed with three doses of PHiD-CV.